Association of clinical practice guidelines with emergency department management of febrile infants ≤56 days of age. Issue 6 (13th February 2015) - Aronson, Paul L.; Thurm, Cary; Williams, Derek J.; Nigrovic, Lise E.; Alpern, Elizabeth R.; Tieder, Joel S.; Shah, Samir S.; McCulloh, Russell J.; Balamuth, Fran; Schondelmeyer, Amanda C.; Alessandrini, Evaline A.; Browning, Whitney L.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Differences among febrile infant institutional clinical practice guidelines (CPGs) may contribute to practice variation and increased healthcare costs. OBJECTIVE Determine the association between pediatric emergency department (ED) CPGs and laboratory testing, hospitalization, ceftriaxone use, and costs in febrile infants. DESIGN Retrospective cross‐sectional study in 2013. SETTING Thirty‐three hospitals in the Pediatric Health Information System. PATIENTS Infants aged ≤56 days with a diagnosis of fever. EXPOSURES The presence and content of ED‐based febrile infant CPGs assessed by electronic survey. MEASUREMENTS Using generalized estimating equations, we evaluated the association between CPG recommendations and rates of urine, blood, cerebrospinal fluid (CSF) testing, hospitalization, and ceftriaxone use at ED discharge in 2 age groups: ≤28 days and 29 to 56 days. We also assessed CPG impact on healthcare costs. RESULTS We included 9377 ED visits; 21 of 33 EDs (63.6%) had a CPG. For neonates ≤28 days, CPG recommendations did not vary and were not associated with differences in testing, hospitalization, or costs. Among infants 29 to 56 days, CPG recommendations for CSF testing and ceftriaxone use varied. CSF testing occurred less often at EDs with CPGs recommending limited testing compared to hospitals without CPGs (adjusted odds ratio: 0.5, 95% confidence interval: 0.3‐0.8). Ceftriaxone use at ED discharge varied significantly based on CPG recommendations. Costs were higher for admitted and discharged infants 29 to 56 days old at hospitals with CPGs. CONCLUSIONS CPG recommendations for febrile infants 29 to 56 days old vary across institutions for CSF testing and ceftriaxone use, correlating with observed practice variation. CPGs were not associated with lower healthcare costs. Journal of Hospital Medicine 2015;10:358–365. © 2015 Society of Hospital Medicine